Study of the risk analysis associated with multimodal maritime transport - Ștefаnov O.; Аgаpe АG.; Stoenciu, D; Berescu, C.; Bocanete, P (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
According to the International Maritime Organization, risk is defined as "a combination of the frequency and severity of the consequence", thus articulating two components of the likelihood of occurrence and the probability of severity of the foreseeable/unpredictable consequences. Risk is a measure of the significance of the hazard that involves a simultaneous examination of its consequences and likelihood of occurrence, using a combination and practical experience, as well as relevant information about the system and its operating environment.